2014
DOI: 10.1371/journal.pone.0097581
|View full text |Cite
|
Sign up to set email alerts
|

Mixed T Helper Cell Signatures In Chronic Rhinosinusitis with and without Polyps

Abstract: In chronic rhinosinusitis (CRS) different phenotypes have been reported based on cytokine profile and inflammatory cell patterns. The aim of this study was to characterize the intracytoplasmatic cytokines ofTcells infiltrating theinflamed sinonasal mucosa.MethodsInfiltrated T cells and tissue homogenates from sinonasal mucosal samples of 7 healthy subjects, 9 patients with CRS without nasal polyp (CRSsNP), 15 with CRS with nasal polyps (CRSwNP) and 5cystic fibrosis patients (CF-NP) were analyzed for cytokine e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
107
3
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(121 citation statements)
references
References 26 publications
5
107
3
6
Order By: Relevance
“…So what, then, is CRSsNP? Although previous studies have suggested that CRSsNP is an adaptive Th1-induced disease process (8)(9)(10), that concept was not confirmed in the current studies. This current investigation is much more extensive than previous work and includes complementary studies simultaneously addressing both tissue and nasal secretions, along with using both proteomics and quantitative transcript expression.…”
contrasting
confidence: 98%
“…So what, then, is CRSsNP? Although previous studies have suggested that CRSsNP is an adaptive Th1-induced disease process (8)(9)(10), that concept was not confirmed in the current studies. This current investigation is much more extensive than previous work and includes complementary studies simultaneously addressing both tissue and nasal secretions, along with using both proteomics and quantitative transcript expression.…”
contrasting
confidence: 98%
“…1 and IFN-g 1 CD4 1 cells in polyps from both groups compared with controls, confirming a recent study from Europe (12). Likewise, they found similar elevations of activated DC subsets (both myeloid DC [mDC] and plasmacytoid DC [pDC]), and these DCs produced equivalent elevated levels of IL-6 and IL12p70 compared with DCs from control tissue.…”
supporting
confidence: 84%
“…The balance in T helper subsets as observed in healthy mucosa is changed in inflamed mucosa. According to flow cytometric analysis of the middle ear in our model, the CD4/CD8 ratio was increased from day 3 to 2 months after inoculation compared to the control group, as Derycke et al (27) reported the CD4/CD8 ratio was increased depending on the severity of inflammation in chronic rhinosinusitis. This result showed that chronic inflammation occurred in the middle ear for a period of 2 months.…”
Section: Discussionmentioning
confidence: 49%